PENETAPAN KADAR AKRILAMIDA PADA NAGET AYAM DENGAN PERBEDAAN PROSES PENGOLAHAN SECARA KROMATOGRAFI CAIR KINERJA TINGGI - Iswandi, Iswandi; Purwantari, Yuniarsih; Widyasti, Jena Hayu (MEDFARM: Jurnal Farmasi dan Kesehatan, 2023)
Acrylamide is a food contaminant that has the potential to cause cancer. Acrylamide is a substance that is formed due to high temperature processing of food such as frying and baking. Chicken nuggets are a popular fast food, easy to get and can be served quickly. This study aims to determine the levels of acrylamide in chicken nugget with variations in processing using frying and oven with High Performance Liquid Chromatography (HPLC). Acrylamide in chicken nuggets is extracted with dichlormethane and ethanol. Measurement of acrylamide levels using High Performance Liquid Chromatography with a Supercolsil C18 column, UV detector at a wavelength of 210 nm and a flow rate of 0.5 mL/min with 85% phosphoric acid as mobile phase in acetonitrile and aquabidest (5:95). Method validation was carried out to determine linearity, accuracy, precision, LOD and LOQ. The results of the method validation were declared valid for the assay as indicated by the linearity value (r) of 0.99947, percent recovery of 97.29% and the results of the precision test obtained an RSD value of 1.36%. The LOD value was 0.3933 ppm and the LOQ was 1.1919 ppm. The results showed that acrylamide can be formed in the processing of chicken nuggets in 3 replications using the oven method with sequential levels of 0.8459 ppm; 0.7936 ppm and 0.7807 ppm. Whereas with the frying method the acrylamide content formed was 1.4591 ppm; 1.4721 ppm and 1.0554 ppm. The results of statistical analysis using the Independent Simple t test showed that there were significant differences with a significance value of 0.028 in the processing with the oven and frying methods.